THE IMPORTANCE OF THE DIGITAL ECONOMY IN INCREASING THE ECONOMIC EFFICIENCY OF INDUSTRIAL ENTERPRISES - Egamberdiev Shavkatbek Shakhobiddin ugli,; Xasanov Kamoldin Zafarjon ugli,; Tavakkalov Salimjon Saydullo ugli, (Лучшие интеллектуальные исследования, 2024)
Anotation. This article discusses the concept of digitization, its role in the development of the economy. The essence of the process of digital transformation, the strategy for implementing this process into the activities of enterprises and the ways of implementing this strategy, the grouping of digital technologies, the advantages and possible losses of the introduction of these technologies, the stages and models of the introduction of a digital enterprise are highlighted and practical recommendations are given.